Financial Innovation and Non-Funded Income of Commercial Bank in Kenya. - Mwai, Gladys Gathoni (University of Embu, 2020)
Technology based financial innovation has had a great impact on the financial industry as a whole over the past few decades. It has presented the banking sector with an opportunity to increase the revenue base. This study intended to identify the impact of technology based financial innovation on non-interest income in Kenya commercial banks. The study investigated how the adoption of ATMs and Cards, Internet and Mobile Banking has impacted the non-interest income of commercial banks in Kenya. Financial innovation has been indicated to affect economic growth and financial inclusion as well as boost the non-funded income of commercial banks (CBK, 2011). Financial innovation has three types which include institutional, process and product. Financial innovation have improved commercial bank income level and further improved their earning and operation by increasing level of non-funded income. The financial innovations are not only adopted to increase their market coverage but also to improve the liquidity and also remain competitive in the market in the current turbulent business environment. Descriptive research design was utilized. The study found that technology based financial innovation has significant effect on the non-interest income earned by commercial banks in Kenya. It recommends all stakeholders in commercial banks to take any investments made towards technology based financial innovation products as a strategy to improve non-funded income.